Threatening Sounds as an Alternative Mitigation Method to Deter Elephant: A Study in Elephant Conservation Centre, Kuala Gandah, Pahang, Malaysia - Norasmah Basari; Mohamad Firdaus Abd Sata; Nor Zalipah Mohamed; Fatin Nursyafiqah Zamri; Haslina Samsudin; Mohd Faizol Shamrie; Muhammad Adhwa Ikhwan Latif; Siti Norzahira Yazid; Aisyah Humairah Mohd Zaidi (Tropical Life Sciences Research, 2025)
Human-elephant conflict is a common issue in the agricultural sector, often resulting in crop damage. This study aimed to evaluate the effectiveness of threatening vocalisation playbacks as a mitigation method to deter elephant encroachment into agricultural areas. The study was conducted at the National Elephant Conservation Centre (NECC) in Kuala Gandah, Pahang, Malaysia, involving two male and five female elephants. Five soundtracks were played to observe the elephants’ responses: the sound of a buzzing bee, a tiger roar, an elephant rumble, rain (control) and nocturnal jungle sounds (control). The elephants’ behaviours were recorded during and after exposure to each soundtrack. The results showed that the elephants responded most strongly to the tiger roar (33%), followed by the buzzing bee sound (23%), while the elephant rumble elicited the fewest responses (8%). The tiger roar and buzzing bee sounds also resulted in the longest halt times, with the elephants stopping and standing still, particularly the older group (p < 0.05). Male and female elephants exhibited similar responses to the sound playbacks (p > 0.05). This study suggests that playback of threatening vocalisations could serve as an additional mitigation strategy to deter elephants from encroaching on agricultural sites, such as oil palm plantations.